Penerapan Media Pembelajaran Audio Visual Dalam Pembelajaran Alkitab: Menggugah Minat dan Keterlibatan Siswa - Sri Rezeki (Pusat Riset dan Inovasi Nasional, 2024)
The use of instructional media in the learning process plays a crucial role in enhancing educational effectiveness. One commonly utilized type of instructional media is audiovisual media, which has proven effective in conveying complex concepts, including within the context of Bible education. This paper discusses the importance and benefits of implementing audiovisual instructional media in Bible education, as well as the challenges faced in its implementation. Through the use of audiovisual media, students can attain deeper understanding, enhance their interest and engagement in learning, and integrate modern technology into the learning process. However, challenges such as resource availability and technical expertise need to be addressed to optimize its benefits.